2011
DOI: 10.1371/journal.pone.0022531
|View full text |Cite
|
Sign up to set email alerts
|

The World's Rediscovered Species: Back from the Brink?

Abstract: Each year, numerous species thought to have disappeared are rediscovered. Yet, do these rediscoveries represent the return of viable populations or the delayed extinction of doomed species? We document the number, distribution and conservation status of rediscovered amphibian, bird, and mammal species globally. Over the past 122 years, at least 351 species have been rediscovered, most occurring in the tropics. These species, on average, were missing for 61 years before being rediscovered (range of 3–331 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 29 publications
(55 reference statements)
2
87
0
Order By: Relevance
“…This frog survived in a remarkably small range and persisted over the last 60 years in an intensively disturbed habitat, undetected despite repeated surveys. The survival of this living fossil is a striking example of resilience to severe habitat degradation during the past century by an amphibian, and may imply on the future survival of this species despite the threat resulting from restricted distribution 23 . Maintaining water and habitat quality at the Hula Nature Reserve, and further research into the natural history of this species, are essential to ensure its survival.…”
Section: Resultsmentioning
confidence: 99%
“…This frog survived in a remarkably small range and persisted over the last 60 years in an intensively disturbed habitat, undetected despite repeated surveys. The survival of this living fossil is a striking example of resilience to severe habitat degradation during the past century by an amphibian, and may imply on the future survival of this species despite the threat resulting from restricted distribution 23 . Maintaining water and habitat quality at the Hula Nature Reserve, and further research into the natural history of this species, are essential to ensure its survival.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we only admit the local extinction of a species after 150 years of no records. According to Scheffers et al (2011), most species rediscovered after a long period without a record were found in less than 150 years after the last report.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have defined as locally Extinct those species which have not been found in the state of Rio de Janeiro and surrounding areas in the last 150 years to reduce the risk of "Romeo error" (see Collar 1998). Following Scheffers et al (2011), most species thought to have disappeared or that have not been seen for extended periods of time were rediscovered after less than 150 years since their last record. We defined as Probably Extinct those species which have not been found in recent decades in the state, but that can still be found in one of the neighboring states (São Paulo, Minas Gerais and Espírito Santo).…”
Section: Methodsmentioning
confidence: 99%
“…Reports of rediscovered species should be published in indexed journals to allow, over time, an evaluation of the relevance and causes of this phenomenon in the context of amphibian conservation (150,152). It will be important for evaluations to adhere to IUCN criteria and previous Red List assessments for a definition of extinct species.…”
Section: Missing Species and The Lazarus Effect: Forgotten Amphibiansmentioning
confidence: 99%